Numerical Analysis of Seepage Field Characteristics for Tunnel Engineering at Shaoquan Lake - WANG Hao; LIU Guang; WANG Jingfeng; ZHANG Xingqi; PU Yubing; YAN Zhong; DING Zhaodong (Renmin Zhujiang)
Waterproofing of the urban under-lake tunnels is directly related to the operation safety of tunnel projects.In order to analyze the waterproof performance of the tunnel,this paper establishes a three-dimensional numerical model of the tunnel under the lake based on the real tunnel structure,simulates the seepage state of the tunnel under different water depths and soil thickness through FLAC3D,and obtains the pore water pressure cloud map of the tunnel under different conditions.It is found that the maximum pore water pressure occurs at the top and outside of the tunnel,so improving anti-seepage measures shall be taken at these areas.After comparison of the anti-seepage performance of the concrete with different impermeable layer thickness by the numerical method,the results show that the anti-seepage performance of the concrete will be significantly enhanced with the increase of impermeable layer thickness.